Strengthening post-market drug surveillance in Nepal: evidence, gaps, and pathways forward - Joshi, Dirgha Raj (Journal of Patan Academy of Health Sciences, 2025)
Nepal has experienced a rising number of pharmaceutical recalls due to quality failures, regulatory non-compliance, and the circulation of substandard and falsified medicines, highlighting critical weaknesses in post-market drug surveillance. Evidence from national recall data shows a persistent increase in recalled products over the past decade, with antimicrobials, analgesics, gastrointestinal medicines, and supplements most frequently affected. However, recall notices alone underestimate the true burden of poor-quality medicines, as delayed detection, limited laboratory capacity, and reactive regulatory processes allow many products to be consumed before corrective action. National surveys and field reports further indicate that quality failures extend across both public and private supply chains. Drawing on Nepal-specific evidence and global literature, this perspective argues that strengthening post-market surveillance requires a shift from recall-driven responses to proactive, risk-based systems. Key pathways forward include expanding routine sampling, enhancing laboratory capacity, improving transparency, adopting traceability tools, fostering regional collaboration, and supporting continuous national medicine-quality research to better protect public health.